QTL analysis of root architecture traits and low phosphorus tolerance in an andean bean population - Cichy, Karen Ann; Blair, Matthew W.; Galeano Mendoza, CH; Snapp, Sieglinde S.; Kelly, James D. (Wiley, 2009)
Tolerance to low P soils is a desirable trait in common bean (Phaseolus vulgaris L.) cultivars grown in acid-weathered soils. Genetic variability in response to P-deficient soils exists in the Andean gene pool. G19833, a low P–tolerant indeterminate Andean landrace, has been evaluated for quantitative trait loci (QTL) and tolerance to low P in combination with Mesoamerican parents. Our goal was to expand our understanding of phenotypic traits and QTL from G19833 expressed in an Andean background. An F5:7 recombinant inbred line (RIL) population developed from two Andean bean genotypes, G19833 and AND696, a determinate line susceptible to low P soils, was examined under low and high soil P levels in replicated field trials. Phosphorus uptake was reduced by 70% and yield by 60% in low P compared to high P treatments. A linkage map was developed with 11 linkage groups and a total length of 1105 cM. Quantitative trait loci for root growth, seed yield, seed P content, and P use efficiency colocalized near the fin gene on linkage group B1. Quantitative trait loci for root growth traits, seed yield, and P uptake colocalized on B11. Quantitative trait loci for root length density (cm cm?3) and root surface area (cm2) did not colocalize with QTL for P uptake. This study indicates that root traits did not play an important role in tolerance to low P soil in an Andean × Andean cross, contrary to previous results with the same P-efficient Andean parent (G19833) crossed to a Mesoamerican bean genotype.